ADMINISTRATIVE ROLE OF PHA IN PUNJAB THROUGH THE LENS OF LEGISLATION: AN INSIGHT - Sarmad Salahuddin; Muhammad Khalid Chauhan; Yasmeen Amir Jafri; Shafqat Ullah (International Journal of Contemporary Issues in Social Sciences, 2024)
Parks and Horticulture Authorities (PHAs) play a vital role in Punjab, Pakistan, by governing public parks, green spaces, urban forests, and plant genetic resources. It was established under the Parks and Horticulture Act of 2012. PHA works toward developing these areas, their maintenance, and their protection. The Punjab Urban and Peri-Urban Forest Policy of 2019 emphasize green space preservation. The botanical gardens in Pakistan, in cities like Lahore, Islamabad, and Peshawar are important for the conservation of plant genetics. PHAs also play an important role in sustainable development, which is done through waste management. It also contributes to Pakistan’s Nationally Determined Contributions. This study examines Pakistan's and Singapore's legislative approaches, focusing on the role of PHAs in urban forestry, the preservation of genetic resources, and sustainable waste management practices. PHA is also making efforts towards smog mitigation, climate improvement minimizing carbon emission and promoting circular economy lowering environmental effects which is important for sustainability. To reach more conclusive insights, the paper will conduct a comparative analysis between Pakistan and Singapore’s legislative and administrative approaches to parks and horticulture. To conclude, the core values of both systems will be observed, by keeping inform the effort and end results achieved by both economies.